Problem-based Learning (PBL) Versus Content-Based Learning (CBL) In The Web-based Environment: an analysis of Malay students' performance in the learning process - Fauziah Sulaiman; Hanafi Atan (2007)
This article reports on the study that explored the differences in Malays students’ performance regarding the learning process provided by the Problem based learning (PBL) approach compared with that of the Content-Based Learning (CBL) approach in the Web-based environment. Both of treatments content the same subject, which is namely ZCT 104-Modern Physics. A group consists of 167 Malays students was given with the two types of treatments. Sixty-seven of the students were treated with PBL and the other-half with CBL treatment. In the end of the treatment both groups will be given with a post-test to see the performance in the learning process. The analysis using the paired-sample t-test reveals that the group that explored the subject with PBL noted higher mark significantly compared to CBL group for the level of confidence p?0.05.